Facial Skin Aging Stages in Chinese Females - Yang, Xiao-xiao; Zhao, Meng-meng; He, Yi-fan; Meng, Hong; Meng, Qing-yang; Shi, Qiao-yin; Yi, Fan (Frontiers in Medicine, 2022)
Background Facial skin is exposed to the environment, which marks it with obvious signs of aging. Based on multi-dimensional non-invasive evaluation data, female facial skin can be characterized in detail. However, there are few studies on the general aging rules of facial skin. Most skin aging studies divide the ages into 5–10-year intervals, so they have lacked dynamic matching with facial skin aging. Aim To explore facial skin aging rules, discuss the main parameters of facial skin aging, propose an unequal-distance aging division method based on the main skin parameters, and study the skin characteristics of Chinese women of different aging stages. Methods We comprehensively described the skin status as 24 non-invasive skin parameters belonging to five dimensions: skin wrinkles, texture, stain, color and barrier function. We performed polynomial fitting on the 21 skin parameters that were significantly correlated with age and derived the rules of aging in the different dimensions. Based on the wrinkle dimension, the facial skin aging process was divided into four stages, and the skin characteristics of the different stages were compared. Results Skin wrinkles increased, texture deteriorated, acne decreased, pigment spots increased, skin tone darkened, and sebum secretion decreased with age, according to the polynomial fitting. The aging stage was divided into an incubation period (18–30 years old), an aging occurrence period (31–42 years old), a rapid aging period (43–47 years old), and a stable aging period (48–60 years old), according to the wrinkles. Different aging stages had different skin characteristics. Conclusion The incubation period is the critical period for the appearance of skin stains; the skin texture gradually deteriorates during the aging occurrence period; the rapid aging period is a critical period for the aging of skin parameters; skin status during the stable aging period is the worst.